ANALISIS KELAYAKAN USAHATANI JAHE (Zingiber officinale) STUDI KASUS DI DESA KEMU KECAMATAN PULAU BERINGIN KABUPATEN OGAN KOMERING ULU SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2019)
Analysis Feasibility of Ginger Farming (Zingiber officinale) Case Study in Kemu Village, Beringin Island, South Ogan Komering Ulu Regency. This study aims: to calculate income and analyze the feasibility of ginger farming (Zingiber officinale) in Kemu village, Pulau Beringin district, South Ogan Komering Ulu Regency. Sampling method is simple random sampling where ginger farmer in Kemu Village, Beringin Kabuapaten Ogan Komering Ulu Selatan Island as many as 46 farmers were taken as many as 32 farmers as sample with the same land area that is 0.25 Ha. The results showed the income of ginger farming (Zingiber officinale) in Kemu village, Pulau Beringin district, Ogan Komering Ulu Selatan Regency is Rp 13,230,708 per hectare per year. And the analysis of R / C ratio of Ginger farming (Zingiber officinale) in Kemu Village, Pulau Beringin District, Ogan Komering Ulu Selatan Regency is 4.1. So the ginger farming is feasible to do.